2011
DOI: 10.1007/s10668-011-9331-7
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming local health through herbal gardens in India: a tool to enhance women active agency and primary health care?

Abstract: In the last few years, an increasing attention has been given to home herbal gardens, especially due to a revived interest in food security and sustainable development. The uses of home herbal gardens and their role in the livelihoods of rural poor uses have been analyzed in the literature. Despite this, few studies focus on the role of home gardens for primary health care and their relevance for the household and women's health. In addition, any analysis has been carried out on the socioeconomic values of hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…On the positive side, see, for instance, the work of Djoudi and Brockhaus (2011) or Boyd (2009) on gender and climate change; Or on landscapes, Colfer et al (2014). Torri (2012) notes the dismal history of agronomic inattention to the typically female-dominated home gardens (also noted by Lopez-Alzina 2007, for Mexico, and repeatedly in the collection by Howard 2003, which included both humid and dry forest areas). But there has been an efflorescence of home herbal gardens in India established mostly by women's self-help groups (190 000 gardens in three states, Tamil Nadu, Karnatak and Kerala).…”
Section: Focus On Products and Fields Of Interest To Womenmentioning
confidence: 87%
“…On the positive side, see, for instance, the work of Djoudi and Brockhaus (2011) or Boyd (2009) on gender and climate change; Or on landscapes, Colfer et al (2014). Torri (2012) notes the dismal history of agronomic inattention to the typically female-dominated home gardens (also noted by Lopez-Alzina 2007, for Mexico, and repeatedly in the collection by Howard 2003, which included both humid and dry forest areas). But there has been an efflorescence of home herbal gardens in India established mostly by women's self-help groups (190 000 gardens in three states, Tamil Nadu, Karnatak and Kerala).…”
Section: Focus On Products and Fields Of Interest To Womenmentioning
confidence: 87%
“…Torri (2010) reports the experience of Indian women, who, as part of their involvement in community-based conservation initiatives, were able to obtain training and other educational opportunities that allowed them to improve living conditions (as well as contributing to the conservation concerns). In another report, Torri (2012) found that Indian women, particularly those from 'scheduled castes' found the creation of home gardens and the related training they received increased their social status at home and in their communities.…”
Section: Educational Opportunitiesmentioning
confidence: 99%
“…Women's health care responsibilities are another frequent 'excuse' for grouping; lower-caste women in India come together to better manage herbal gardens (Torri 2012): 'Over the last 15 years, more than 190 000 home herbal gardens have been established by the community-based organisations, which are mainly women's self-help groups in more than 6000 villages and hamlets across the states of Kerala, Karnataka and Tamil Nadu'.…”
Section: Alternative Gendered Livelihood Pathsmentioning
confidence: 99%
See 2 more Smart Citations